Application of a Pbl-Based Modules to Increase Critical Thinking Skills and Independence Learning - Kharismawan, Bhakti; Haryani, Sri; Nuswowati, Murbangun (Postgraduate, Universitas Negeri Semarang, Indonesia, 2018)
This study aims to measure the effect of application of Problem Based Learning (PBL) based module to critical thinking skill and student learning independence related to reaction rate material. PBL-based module is a module that can make students think actively in searching and finding answers from a problem. This type of research is an experiment. The research design used is posttest design and sampling technique using purposive sampling. The research instruments used were: cognitive test to measure students' critical thinking skill, questionnaire of learning independence, and questionnaire of student response to learning. Quantitative analysis result of experiment class score is 77,49 with 25 complete student from 28 students and control class has average 73,62 with 22 students complete from 29 students. Correlation test obtained correlation number of 0.37 and test the coefficient of determination obtained a number of 14.31%. Qualitative analysis found that overall showed that the experimental class was better than the control class. Thus it is concluded that the application of PBL-based module affect the improvement of critical thinking skills and student independence learning.